Media Education: From A Defence Project to an Empowerment Project - Boulkaibet, Ahlem; Boulkaibet, Idris (Journal of Human Sciences, 2021)
This article discusses the challenges posed by new information technologies and their repercussions for education. Creating new methods has become imperative for young people to sift through media content. The challenge is to know how to make young people more vigilant. The approach is based on making young people both more careful and more interactive in an increasingly powerful virtual environment by giving them skills without which message filtering would not be possible. Therefore, the adoption of new methods of education would become necessary to face these emerging challenges. In view of these challenges, the article attempts to provide an answer to the question: what can be done to make education more positive by awakening the faculty of criticism in young people?